2020
DOI: 10.1111/cas.14337
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell‐derived angiopoietin‐like protein 2 establishes a preference for glycolytic metabolism in lung cancer cells

Abstract: We previously revealed that tumor cell-derived angiopoietin-like protein 2 (ANGPTL2) accelerates the metastatic capacity of tumors in an autocrine/paracrine manner by activating tumor cell motility and invasiveness and the epithelial-mesenchymal transition. However, the effects of ANGPTL2 on cancer cell glycolytic metabolism, which is a hallmark of tumor cells, are unknown. Here we report evidence supporting a role for tumor cell-derived ANGPTL2 in establishing a preference for glycolytic metabolism. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Angiopoietin-like protein 2 (ANGPTL2) is a secreted factor that can have both autocrine and paracrine effects and it is involved in cell motility and invasiveness. In different lung cancer (LC) cellular models (NCI-H460, NCI-H460-LNM35, NCI-H1975, and HCC15), ANGPTL2 is responsible for an increase in GLUT3 expression (and an increase in glycolytic flux) via an integrin α5β1/ERK-dependent pathway impinging on TGFβ and its downstream factor ZEB1, concurrently with the execution of the EMT ( Figure 3 ) [ 172 ]. ANGPTL2 → integrin α5β1→ERK ⇒ TGFβ ↑ ⇒ ZEB1 ↑ ⇒ (GLUT3 ↑ & EMT) …”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%
“…Angiopoietin-like protein 2 (ANGPTL2) is a secreted factor that can have both autocrine and paracrine effects and it is involved in cell motility and invasiveness. In different lung cancer (LC) cellular models (NCI-H460, NCI-H460-LNM35, NCI-H1975, and HCC15), ANGPTL2 is responsible for an increase in GLUT3 expression (and an increase in glycolytic flux) via an integrin α5β1/ERK-dependent pathway impinging on TGFβ and its downstream factor ZEB1, concurrently with the execution of the EMT ( Figure 3 ) [ 172 ]. ANGPTL2 → integrin α5β1→ERK ⇒ TGFβ ↑ ⇒ ZEB1 ↑ ⇒ (GLUT3 ↑ & EMT) …”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%
“…TGF-β signaling pathway plays a pivotal role in inducing EMT. In lung cancer cells TGF-β could upregulate SLC2A3 expression through the EMT gene ZEB1 [ 59 ]. However, the link between TGF-β signaling and SLC2A3 expression is much less addressed and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell-derived angiopoietin-like protein 2 (ANGPTL2) activates tumor cell motility, invasiveness, and epithelial-mesenchymal transition to accelerate tumor metastasis in an autocrine/paracrine manner [ 36 ]. Recently, novel research indicated that stroma-derived ANGPTL2 could drive the production of immune-stimulated macrophages through the NF- κ B pathway and accelerate the activation of CD4 T helper 1 (Th1) cells to play an antitumor role [ 37 ].…”
Section: Discussionmentioning
confidence: 99%